2020
DOI: 10.1212/nxg.0000000000000394
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathologic description of CHCHD10 mutated amyotrophic lateral sclerosis

Abstract: ObjectiveTo present the postmortem neuropathologic report of a patient with a CHCHD10 mutation exhibiting an amyotrophic lateral sclerosis (ALS) clinical phenotype.MethodsA 54-year-old man without significant medical history or family history presented with arm weakness, slowly progressed over 19 years to meet the El Escorial criteria for clinically probable ALS with bulbar and respiratory involvement, and was found to have a CHCHD10 p.R15L mutation. Postmortem neuropathologic examination took place including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
1
13
2
Order By: Relevance
“…We previously exploited this to infer C9ORF72 repeat expansion genotypes [56,66] through neuropathological screening of our New Zealand ALS cases [38]. Mutant SOD1 [67,68], FUS [44], and certain other genotypes [69,70] can also be inferred from neuropathology. However, for many ALS/FTD genes -particularly those such as TARDBP, SQSTM1, and UBQLN2 that encode proteins already within the hallmark TDP-43 inclusions -no completely discriminating neuropathology has been reported [42,69,[71][72][73][74][75].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously exploited this to infer C9ORF72 repeat expansion genotypes [56,66] through neuropathological screening of our New Zealand ALS cases [38]. Mutant SOD1 [67,68], FUS [44], and certain other genotypes [69,70] can also be inferred from neuropathology. However, for many ALS/FTD genes -particularly those such as TARDBP, SQSTM1, and UBQLN2 that encode proteins already within the hallmark TDP-43 inclusions -no completely discriminating neuropathology has been reported [42,69,[71][72][73][74][75].…”
Section: Discussionmentioning
confidence: 99%
“…Mutant SOD1 [67,68], FUS [44], and certain other genotypes [69,70] can also be inferred from neuropathology. However, for many ALS/FTD genes -particularly those such as TARDBP, SQSTM1, and UBQLN2 that encode proteins already within the hallmark TDP-43 inclusions -no completely discriminating neuropathology has been reported [42,69,[71][72][73][74][75]. This has hampered the validation of pathogenicity of novel variants in these genes, in turn obscuring understanding of protein domains and molecular processes important to ALS/FTD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent description of the human pathology of CHCHD10 p.R15L-ALS describes anterior horn neuronal CHCHD10-positive, TDP-43-negative protein aggregates ( Keith et al., 2020 ). Such aggregates are not apparent in the CHCHD10-R15L transgenic mice, but p62-positive, TDP-43-negative punctate staining is apparent in the spinal cord, indicating that the mice display some deficit in CNS protein degradation.…”
Section: Discussionmentioning
confidence: 99%
“…In these cell types, SOD1 aggregates are found in the cytosol, but also within mitochondria, thus creating oxidative stress [ 41 , 42 ]. Other ALS gene products have been identified that produce proteins controlling mitochondrial protein import (coiled-coil-helix-coiled-coil domain protein 10, CHCHD10, [ 43 ]), the cytoskeleton (e.g., Profilin-1, ALS18 ), mRNA stability (e.g., Fused in sarcoma, FUS, ALS6 ), and protein trafficking (e.g., valosin-containing protein, VCP, ALS14 ) [ 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%